Penerapan Bilateral Filtering untuk Peningkatan Kualitas Citra Digital Fokus pada Gaussian, Salt-and-Pepper, dan Speckle Noise - Dermawan, Andre; Tommy, Tommy; Handoko, Divi (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2024)
The main objective of this research is to improve the quality of digital images without losing important details, such as object edges, while also developing efficient and user- friendly software for image processing. Bilateral filtering is a non-linear filtering method used to reduce noise in images while preserving edge details. This filter works by combining smoothing based on spatial proximity and pixel intensity similarity. Thus, bilateral filtering is effective in reducing noise without blurring the important edges of the image. This research develops an application that can open, process, and save digital images, allowing users to practically reduce noise in images. The results show that bilateral filtering can significantly enhance digital image quality with substantial noise reduction, although certain types of noise may require further parameter adjustments for optimal results. Keywords: Bilateral Filtering, Digital Image, Noise, Visual Basic, Image Processing.